Nursing Warmth Scale (NWS): Development and empirical validation - zita Lagos; Cibele Andrucioli de Mattos Pimenta; María Teresa Urrutia (Universidad Nacional de Colombia, 2022)
Objective: To construct and validate the Nursing Warmth Scale (NWS) through the development of a standardized measurement of nurses' warmth, perceived from the perspective of patients, and identify the behaviors and factors associated with this feeling of warmth. Materials and methods: The NWS was developed following the scale construction methodology under a triphasic model. The construction of items was elaborated based on the results of a previously published integrative review that consolidated the construct and the related variables. A qualitative phase was also incorporated to evaluate the latent variable. Content validity was assessed with 10 expert judges. An item try-out was conducted with 476 patients in health institutions. Exploratory factor analysis -through the common factor method and oblique rotation- was used for the item reduction process. Results: The construct "Nursing Warmth" was established after the theoretical and empirical phases of the study. The literature review and interviews with 23 patients and 25 nursing professionals provided a set of behaviors divided into 2 categories: verbal and nonverbal behaviors. Exploratory factor analysis allowed identifying 5 factors and 35 items. The reliability was estimated through Cronbach's alpha. The identified factors are: F1-Nonverbal connection-relationship with the other (0.943), F2-Empathy (0.909), F3-Verbal connection-relationship with the other (0.914), F4-Inclusion (0.858), and F5-Confidence (0.852). The Tucker-Lewis Index was 0.901. Conclusions: The NWS demonstrates evidence of reliability and validity. This tool may be useful in clinical settings and for teaching and research addressing interpersonal nursing skills.